Attitudes about the use of internet support groups and the impact among parents of children with Cornelia de Lange syndrome. Issue 2 (10th May 2016) - Cacioppo, Cara N.; Conway, Laura J.; Mehta, Devanshi; Krantz, Ian D.; Noon, Sarah E.
Abstract : There is an abundance of information in the literature on patient experiences with Internet support groups (ISGs). However, studies exploring these experiences in a rare disease population are scarce, even though these families are often at a disadvantage for resources, reliable information, and support. The aim of the current study was to explore the experiences with ISGs for parents of children with Cornelia de Lange syndrome (CdLS), a rare genetic diagnosis, in order to better understand the impact on emotional support and their child's medical care. Focus groups were conducted to inform the design of a large‐scale internet survey. The survey asked parents closed‐ and open‐ended questions regarding experiences with ISGs, with a focus on the psychosocial, medical, and logistical aspects. The survey found that 141/170 (82.6%) respondents have visited an Internet‐based support group to find support or information about their child's CdLS diagnosis. The majority of respondents (71.7%) reported that ISGs have been helpful in finding emotional support, with the most common areas impacted as a result of ISG participation being behavior toward their children and family dynamic. Regarding medical care, most respondents (63.9%) reported that ISGs have been helpful in finding medical information and support, with the most commonly impacted areas of their child's care including day‐to‐day management, diet, therapy interventions, and healthcare providers. These findings provide a greater understanding of the role of Internet networking in healthcare and may inform future approaches to medical care and psychosocial support for rare, complex genetic diagnoses. © 2016 Wiley Periodicals, Inc.